Integrating arts into nature education for sustainable rural development - Yiqiu, Su; Maulan, Suhardi (John Wiley and Sons, 2026)
Rural environments offer abundant ecological and cultural resources that support the development of nature education, but practical challenges persist in fully utilising these local resources. Building on this context, the study examines an arts-integrated nature education curriculum implemented in Jianlou Village, Hunan Province, to explore how artistic practices can enrich rural nature-based learning. Using qualitative analysis, 49 documents—including teaching plans, student artworks, field observation notes and reflective journals—were coded and analysed using NVivo. Research indicates that art can be integrated into three key domains: site preparation, instructional approaches and curriculum materials. This integration deepens learners' engagement with the rural environment, enhances the quality of nature education activities and advances local educational development. The framework provides theoretical insights and practical guidance for curriculum innovation, teacher professional development and the advancement of art-integrated nature education in rural communities.